Exploring how Nigerian women foster action to be taken to involve more women participation in technical and vocational education - Akor, Robert Thomas; Bakar, Ab. Rahim; Hamzah, Azim; Mat Rashid, Abdullah (Australian International Academic Centre, 2015)
Despite the documented benefits to economic and social development of women and the constitutional guarantee for equal right under the law to all citizens, the advancement of the status of women in Nigeria is still far from satisfactory. The participation of women in technical and vocational education is abysmally low. Recent literature describing education of women in technical and vocational education in Nigeria, still need more equality of access to the program. As the Nigerian transition to knowledge economy, information age and vision 20:2020 technologically literate workforce is vital. Likewise the contribution of women to technical and vocational education profession in vital, yet the number of women considering entering historically dominated profession remain at unacceptable level. Employment prospects for women have increased dramatically in the late 20th century. Yet in technical and vocational education profession, a profession that holds promise and opportunity for one to positively impact society-the lack of women in the field seems baffling. In order to examine how Nigerian women foster action to be taken to resolve misrepresentation of women in technical and vocational education in Polytechnic institution a study was important. The purpose of this study was to identify action to be taken so that more women can participate in the program from the perspective of women who are currently enrolled in technical and vocational education program in Polytechnic institution. One major Polytechnic was selected with twelve participants. The descriptive and exploratory research analyzed the interview responses of the participants in order to examine their perceptions. Recommendations made as a result of this study include: a need to formulate specific strategies, policy and program to promote women participation in technical and vocational education, women representation in policymaking bodies; increase number of women lecturers; encourage women to participate in traditionally male dominated technical and vocational fields; conduct nontraditional student support groups and peer counseling; provide nontraditional role model and give preference to female student with regards to recruitment.